Seasoned Equity Offering and Financial Reporting Quality - Mahmoud Nasiri (Shahid Bahonar University of Kerman, 2020)
Objective: This study explores the impact of seasoned equity offering (SEO) on financial reporting quality (FRQ), using free cash flow and growth opportunities, considering the cost of capital. Financial reporting quality is a potential factor in reducing information asymmetry between managers and shareholders of the companies. Method: We used two samples of the companies listed in the Tehran Stock Exchange from 2001 to 2018. The principal sample consists of the companies that had seasoned equity offerings, and the parallel sample consists of the companies that are in the same industry and did not have SEO. The principal sample consists of 1543 company-year observations, and the parallel sample consists of 1938 company-year observations. We used two methods to calculate growth opportunities, the market-to-book value ratio, and Hyland and Diltz (2002) method. Free cash flow (FCF) was estimated using the Richardson (2006) method. To examine the role of cost of capital,  we used the five-factor model of Fama and French (2015). Financial reporting quality was estimated using the methods of Dechow and Dichev (2002) and McNichols (2002). To test the hypotheses, we estimated multivariate linear regressions using the findings of Dechow and Dichev (2002), Doyle et al. (2007), and Huang et al. (2012) and the portfolio formation approach. Results: Given that there are various measurements of  financial reporting quality and there is no universally accepted way of the measurement of financial reporting quality, the results showed that the companies with high free cash flow and low growth opportunities and those with low free cash flow and high growth opportunities increase their financial reporting quality when seasoned equity offering. The companies with higher cost of capital have higher financial reporting quality compared with those with lower cost of capital, and when seasoned equity offering, the companies with lower cost of capital increase their financial reporting quality. The results also showed that while the companies without capital raising have high free cash flow and low growth opportunities, they have low financial reporting quality, and while the companies have low free cash flow and high growth opportunities, they have high financial reporting quality. Conclusion: Companies that accept seasoned equity offerings increase the quality of their financial reporting to attract more funding and succeed in underwriting new stocks.